2018
DOI: 10.5897/ajmr2018.8843
|View full text |Cite
|
Sign up to set email alerts
|

Response of microbial communities to oil spill in the Gulf of Mexico: A review

Abstract: Crude oil has become a part of the marine ecosystem through natural seeps and oil spills. Microbial communities have adopted various response mechanisms to adjust to oil spills that contaminate the marine environment and help restore the ecosystem to its original state. These response mechanisms ranges from change in indigenous microbial community composition, change in microbial diversity to gene diversity and modification. An instance for review was the deep-water horizon (DWH) oil spill in the Gulf of Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Previous mesocosm experiments using water from the sGoM have demonstrated the significant role of the genus Alteromonas in hydrocarbon degradation within this region (Régimbeau et al, 2021). While this outcome diverges from reports concerning the nGoM, where the most commonly reported genera for hydrocarbon degradation are Alcanivorax, Cycloclasticus and Colwellia (Hazen et al, 2016;Kimes et al, 2014;Linda et al, 2018), the genus Alteromonas appears to hold greater significance in the sGoM. The measurements obtained for alkB and CHB in bottom water (Table 3) suggest that the greatest degradation activity occurs in surface water.…”
Section: Estimation Of Hydrocarbon Degradation Activity and Detection...mentioning
confidence: 76%
“…Previous mesocosm experiments using water from the sGoM have demonstrated the significant role of the genus Alteromonas in hydrocarbon degradation within this region (Régimbeau et al, 2021). While this outcome diverges from reports concerning the nGoM, where the most commonly reported genera for hydrocarbon degradation are Alcanivorax, Cycloclasticus and Colwellia (Hazen et al, 2016;Kimes et al, 2014;Linda et al, 2018), the genus Alteromonas appears to hold greater significance in the sGoM. The measurements obtained for alkB and CHB in bottom water (Table 3) suggest that the greatest degradation activity occurs in surface water.…”
Section: Estimation Of Hydrocarbon Degradation Activity and Detection...mentioning
confidence: 76%
“…In the natural environment, it has been observed that the initial microbial community can contribute to up to 19% of the oil-degrading bacterial community [39]. Initial bacterial communities prior to an oil spill, in particular the naturally present oil-degrading microorganisms, may be important in controlling the development of oil-degrading communities [158]. Recent studies have identified bacteria from more than 79 genera that have the capabilities to degrade petroleum hydrocarbons [159].…”
Section: Bacterial Communitymentioning
confidence: 99%
“…In polluted sites, hydrocarbons undergo biodegradation by actions of natural bacterial populations capable of utilizing these compounds as carbon and energy sources (Bacosa et al 2016;Adzigbli et al 2018;Dominguez et al 2019;. Upon the introduction of hydrocarbons, the natural micro ora shifts to favor the growth of oil-degrading bacterial populations and often result in a signi cant shift in community structure (Severin et al 2016;Gemmell et al 2018;Bacosa et al 2018;Kamalanathan et al 2019;Steichen et al 2020).…”
Section: Introductionmentioning
confidence: 99%